Outpatient palliative medicine consultations: urgent or routine?. Issue 2 (11th June 2020) - Alam, Sorayya; Pope, Ashley; Le, Lisa; Al-Awamer, Ahmed; Banerjee, Subrata; Lau, Jenny; Mak, Ernie; Zimmermann, Camilla; Hannon, Breffni
Abstract : Background: Although outpatient palliative care clinics (OPCCs) provide a venue for early, pre-emptive referral to palliative care on a routine basis, some patients will continue to require urgent referrals. The purpose of this study was to characterise these urgent referrals to determine whether they reflect clinical need or convenience. Methods: We retrospectively compared new patients in an OPCC who were seen urgently versus those seen at routine appointments. Descriptive statistics compared the two groups in terms of clinical characteristics, referring teams, symptoms, performance status and outcomes. Logistic regression was used to identify factors associated with urgent referral to the OPCC. Overall survival was compared using the log-rank test. Results: Between January 2016 and December 2017, a total of 113 urgent referrals were reviewed in the OPCC; these were compared with a random sample of 217 routine referrals. Patients seen urgently were more likely to be referred by surgical oncology, and to report worse symptom scores for pain (p=0.0007), tiredness (p=0.02), well-being (p=0.001), constipation (p=0.02) and sleep (p=0.01). More patients seen urgently required direct admission to hospital following the visit (17.7% vs 0.9%, p<0.001). Median survival was shorter for patients seen urgently (4.3 months, 95% CI 3.4 to 7.8) versus routinely (8.1 months, 95% CI 7.2 to 9.5). Conclusions: Compared with routine referrals, new patients seen urgently in the OPCC had higher symptom burden, shorter median survival and a greater chance of direct admission to hospital. Palliative care clinics should consider how best to accommodate urgent referrals.